Violympic toán 8

DC

Tìm GTLN cùa

B = \(\frac{x^2-6x+14}{x^2-6x+12}\)

DH
28 tháng 12 2019 lúc 15:25

\(B=\frac{x^2-6x+14}{x^2-6x+12}\)

\(B=\frac{x^2-6x+12+2}{x^2-6x+12}\)

\(B=1+\frac{2}{\left(x-3\right)^2+3}\le1+\frac{2}{3}\)

\(B=1+\frac{2}{\left(x-3\right)^2+3}\le\frac{5}{3}\)

Dấu " = " xảy ra \(\Leftrightarrow x=3\)

Bình luận (0)
 Khách vãng lai đã xóa
TL
28 tháng 12 2019 lúc 15:30

B=\(\frac{x^2-6x+14}{x^2-6x+12}\)

=\(\frac{x^2-6x+9+3+2}{x^2-6x+9+3}\)

=\(\frac{\left(x^2-6x+9\right)+3+2}{\left(x^2-6x+9\right)+3}\)

=\(\frac{\left(x-3\right)^2+3+2}{\left(x-3\right)^2+3}\)

=\(\frac{\left(x-3\right)^2+3}{\left(x-3\right)^2+3}+\frac{2}{\left(x-3\right)^2+3}\)

=1+\(\frac{2}{\left(x-3\right)^2+3}\)

*Ta có:(x-3)2 \(\ge\) 0;với mọi x;cộng 3 vào 2 vế

\(\Rightarrow\)(x-3)2+3 \(\ge\) 0+3;với mọi x

\(\Rightarrow\)(x-3)2+3 \(\ge\) 3;với mọi x

\(\Rightarrow\)\(\frac{2}{\left(x-3\right)^2+3}\) \(\ge\) 0;với mọi x;lấy hai vế cộng cho1

\(\Rightarrow\)\(1+\frac{2}{\left(x-3\right)^2+3}\)\(\ge\)1+0;với mọi x

Vậy .................................

Bình luận (0)
 Khách vãng lai đã xóa